Enhancing Students’ Communication Skills Through Journalism-Based Learning Media in Social Studies: A Study of Class VIII-D at MTsN 1 Medan - Hayani, Rika Nanda; Ponidi, Ponidi (Journal of Social Work and Science Education, 2025)
This study examines the application of journalism-based learning media in social studies education to enhance the communication skills of eighth-grade students (class VIII-D) at MTsN 1 Medan. It focuses on developing students’ abilities to convey messages effectively through oral and written forms, as well as managing news content. A qualitative research design with a descriptive analytical approach was employed. The study involved direct engagement between researchers and participants (students and teachers) to collect in-depth data on the implementation and outcomes of journalism-based learning activities. The findings demonstrate that journalism-based learning media, such as school wall magazines and digital magazines, significantly improved students’ communication skills. Participants showed enhanced ability to articulate messages, write news, and manage media content, fostering a more interactive and engaging learning process. This study introduces an innovative approach to social studies education by integrating journalism techniques into classroom learning, bridging the gap between theoretical knowledge and practical communication skills. The results suggest that incorporating journalism-based media in curricula can revitalize traditional teaching methods. Educators are encouraged to adopt such creative tools to promote active learning and student participation. The research contributes to pedagogical strategies by highlighting the effectiveness of journalism-based media in nurturing critical thinking, creativity, and communication competencies among students, offering a replicable model for similar educational settings.